PENGARUH RISIKO KREDIT TERHADAP PROFITABILITAS BANK UMUM KONVENSIONAL (PERIODE 2019-2021) - Tahira, Zahra; Widiastuty, Tri (Review of Accounting and Business, 2023)
The growth of Conventional Commercial Banks listed on the Indonesia Stock Exchange for the 2019-2021 period has fluctuated, tending to decrease in terms of profitability; this is vertically proportional to credit risk, which has increased in the research period. This research aims to determine the effect of credit risk on profitability in Conventional Commercial Banks listed on the Indonesia Stock Exchange for the 2019-2021 period. The method used in this research is a descriptive and verification method with secondary data obtained from financial reports and annual reports. The population in this research is conventional banks listed on the Indonesia Stock Exchange (BEI) for the 2019-2021 period. The sampling technique used was purposive sampling with a sample of 14 banks. The data analysis technique used is simple regression analysis. The results of this research show that partially credit risk has a negative and significant effect on profitability with a significance level of 5%. The profitability variable is influenced by the credit risk condition variable by 9%, while the remaining 91% is influenced by other factors not explained in this research.